ANALISIS PENGARUH DIMENSI â DIMENSI KUALITAS LAYANAN TERHADAP LOYALITAS PELANGGAN PADA KRANGGAN AJI MOTOR AHASS 0367 KABUPATEN KENDAL - Miftakul Khoir, 09.05.51.0087; Wuryan, Sophiyanto (Students Journal of Economic and Management, 2014)
Quality is a dynamic state associated with products, services, people, processes and environments that meet or exceed expectations. Loyalty is defined is a consumer impulse to forge strong ties with the company, the bonding is done with customer loyalty by using the goods or services that have been worn. The concept of service quality include reliability, responsiveness, assurance, tangible concern and has become a dominant factor to the success of the company. The purpose of this study was to determine and analyze whether tangible, reliability, responsiveness, assurance and concern for quality of service and a significant positive effect on customer loyalty in 0367 AHASS Kranggan Aji Motor Kendal.The type of data this study used primary data. The population in this study is 0367 AHASS customers Kranggan Aji Motor Kendal November 2012 until October 2013 as many as 9,124 customers. The sample used in this study was 99 respondents. Analysis of the results of the study of 99 respondents AHASS 0367 Kranggan customers Aji Motor Kendal on service quality acquired intangible value of the regression coefficient of 0.511 is positive and significant effect (p = 0.000 < 0.05), the reliability values obtained by regression coefficient 0.269 is positive and significant effect (p = 0.000 < 0.05), responsiveness obtained regression coefficient of -0.122 is negative and significant effect(p = 0.037 < 0.05), certainty is obtained regression coefficient of 0.200 is positive and significant effect (p = 0.000 < 0.05) and the regression coefficient values obtained awareness of 0.268 is positive and significant effect (p = 0.000 < 0.05). Thus tangible, reliability, certainty and concern for the quality of service and a significant positive effect on customer loyalty in 0367 AHASS Kranggan Aji Motor Kendal whereas responsiveness toÂ service quality and a Â significant negative effect on customer loyalty in 0367 AHASS Kranggan Aji Motor Kendal.Keywords: Service Quality of Dimension, Customer Loyalty, Services Products